Seasonal and Spatial Production Patterns of Dissolved Inorganic Carbon and Total Alkalinity in a Shallow Beach Aquifer - Kim, Kyra H.; Heiss, James W.; Michael, Holly A.; Ullman, William J.; Cai, Wei-Jun (Frontiers in Marine Science, 2022)
Dissolved inorganic carbon (DIC) and total alkalinity (AlkT) fluxes to the nearshore ocean can directly impact the rates of primary production, coral reef formation, coastal ocean acidification, and continental shelf ecology. Current understanding of the transformations that DIC and AlkT undergo as they move from land to sea are limited, leading to difficulties in estimating future DIC and AlkT export that may be altered under a changing climate. While much research has focused on carbon fluxes in carbon-rich mangroves and coastal wetlands, DIC and AlkT transformations and distributions in sandy beach aquifers, which are comparatively carbon-poor, have not been studied as extensively. We monitored DIC and AlkT concentrations in a sandy beach system over six sampling events spanning two years. Substantial changes to DIC and AlkT occurred along subsurface flowpaths due to aerobic respiration and anoxic reactions, resulting in an additional mean flux to the ocean of 191 and 134 mmol/d per meter length of shoreline, respectively. The chemical alterations occurred within the saltwater-freshwater mixing zone beneath the beach surface. Both aerobic and anaerobic reactions actively contributed to DIC and AlkT production within the system, as indicated by DIC: AlkT and dDIC:dAlkT ratios relative to the theoretical dilution line. The work indicates that beach aquifers support active transformation of inorganic carbon and highlights a potentially important and overlooked source of DIC and AlkT to coastal systems.